Analisis Perbandingan Hasil Pengukuran Detak Jantung dan SPO2 Dengan Sensor MAX30100 Berbasis Mikrokontroler Atmega328P dan Pulse Oximeter - Rizky Wijaya, Aura; Dhiyaa' Marda, Muhammad; Taryudi; Sari, Churnia (LPPM Universitas Negeri Jakarta, 2026)
Heart rate is an important indicator for assessing an individual’s health condition. Measuring heart rate is essential to detect changes in physical health, particularly during physical activities such as exercise. This study aims to design and develop a heart rate monitoring system using the optical sensor MAX30100 based on the Arduino Atmega328P platform. The sensor is utilized to detect changes in blood volume at the fingertip using the photoplethysmography (PPG) method. The data obtained from the sensor are processed by the microcontroller to calculate the heart rate value in beats per minute (BPM), which is then displayed on a 16x2 I2C LCD screen, allowing users to directly observe the measurement results.